2012
DOI: 10.1007/s00482-012-1241-6
|View full text |Cite
|
Sign up to set email alerts
|

Medikamentöse Therapie der Angst bei Patienten mit fortgeschrittenen Tumorerkrankungen bzw. Patienten in der palliativen Situation

Abstract: With the existing evidence no general recommendations for pharmacological treatment of anxiety in palliative care can be given. Even for the commonly used benzodiazepines, neuroleptics, antidepressants, antihistamines and beta blockers for the treatment of anxiety no evidence based recommendations can be made. However, these medications are commonly used to treat anxiety in other patient populations and can also be used in palliative care patients. According to our review we cannot recommend a single drug or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Also, as part of the statistical analysis multiple tests were carried out without adjustments as it was an exploratory analysis. Finally, the survey was conducted in 2014 and it is possible that there have been changes in practice since, particularly as new or updated guidelines (for cancer patients and the general population) were produced shortly before and after the data collection [ 18 – 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, as part of the statistical analysis multiple tests were carried out without adjustments as it was an exploratory analysis. Finally, the survey was conducted in 2014 and it is possible that there have been changes in practice since, particularly as new or updated guidelines (for cancer patients and the general population) were produced shortly before and after the data collection [ 18 – 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…13–15 As a consequence, sparse evidence from RCTs and observational studies has been identified for relevant areas of symptom treatment. 1621…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 33 Consequently, effective SICs require that clinicians continuously empathize, by which we mean anticipate, appreciate, validate, and explore the emotions the conversations evoke. 34 , 35 , 36 , 37 Although strong patient emotions are uncomfortable for most clinicians, it is neither empathic nor productive to comfort patients or family members by avoiding, minimizing, or suppressing them. On the contrary, strong emotions are to be expected, and they may actually be evidence of clinician authenticity, skill, and compassion.…”
Section: Introductionmentioning
confidence: 99%